Chauvinistic Features in The Designs of Political Propaganda Posters (Al-Academy, 2024)
Based on the danger of chauvinism and the strife, conflicts and disagreements it raises among society and its expansion due to the development of global network communications, and the importance of posters as an effective visual artistic means that addresses the public, especially those posters that specialize in complex functional performance, such as propaganda posters spread across the Internet, and specifically political propaganda posters, The researcher’s motivation to stop at the topic of “chauvinism” in the designs of propaganda posters, due to its role in changing the convictions of public opinion and trying to lead it according to planned paths and directions, and his desire to identify and introduce the chauvinistic features in the designs of these posters spread across the Internet. He formulated the problem of his research in the first chapter with a question. : (What are the chauvinist features in the designs of political propaganda posters?) Its goal was (to identify the chauvinist features in the designs of political propaganda posters), reviewing the importance of research at both the theoretical and applied levels. The second chapter included the theoretical framework, divided into two sections: (chauvinism and its intellectual references, and chauvinist mechanisms in designing the advertising poster). In the first section, it dealt with an introduction to learning about the concept of chauvinism, its goals, and its methods in designing political propaganda posters. The second section also dealt with the chauvinistic implication in the poster and the chauvinistic techniques employed in it, as well as chauvinist propaganda and its communicative message in the poster.In the third chapter, the researcher determined his research methodology by using the descriptive approach to analyze sample models, which was represented by a research sample that included (5) posters from the research community, which was limited to (20) posters that participated in a virtual exhibition on the Internet whose topic was focused on political propaganda for the current Russian-Ukrainian war.